1994
DOI: 10.1111/j.1469-7610.1994.tb01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Reliability in Psychiatric Surveys of Children Aged 6–12

Abstract: The reliability of young children's self reports of psychiatric information is a concern of epidemiologists and clinicians alike. This paper explores the determinants of test-retest reliability in a sample of children from the general population using reliability coefficients constructed from a kappa statistic. Age, cognitive ability, and gender are related to consistency of reports in a test-retest paradigm. Controlling for age, cognitive ability and gender, children report more reliably on observable behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 14 publications
1
36
1
Order By: Relevance
“…According to Cohen,31 a sample size of 300 generates a standard error of 0.10 or less, when the kappa is 0.40 and the prevalence is 10% or more. To reach this prevalence level, each subsample would need to include about 25% of children from psychiatric clinics, 32 the others being drawn from the community.…”
Section: Participantsmentioning
confidence: 99%
“…According to Cohen,31 a sample size of 300 generates a standard error of 0.10 or less, when the kappa is 0.40 and the prevalence is 10% or more. To reach this prevalence level, each subsample would need to include about 25% of children from psychiatric clinics, 32 the others being drawn from the community.…”
Section: Participantsmentioning
confidence: 99%
“…Given these limitations, there is a real question about whether the young child's self-perceptions, memories, feelings, and reported behavior can be reliably assessed through self-report. Although limited, studies on the use of interview techniques among young children show that their replies are unreliable [Achenbach et al, 1987;Breton et al, 1995;Edelbrock et al, 1985;Fallon and Schwab-Stone, 1994;Schwab-Stone et al, 1994]. In contrast, Faraone et al [1995] and others have shown maternal reports of psychopathology to reach high levels of reliability, even over a 1-year period.…”
Section: Methodsmentioning
confidence: 92%
“…Nonetheless, Grills and Ollendick (2003) have suggested that children younger than 10 may not have the ability to describe their feelings and behaviors accurately. As children age, they may become better informants (Kraemer et al, 2003) and their self-reports may become more reliable (Fallon and Schwab-Stone, 1994). There is little consensus about how to reconcile data from multiple informants.…”
Section: Reconciling Results Across Multiple Informantsmentioning
confidence: 99%